A Self determination theory based exercise intervention in a group of adult exercisers : a contextual evaluation - Kaminski, Karoline (2010)
ABSTRACT Karoline Kaminski. 2010. A Self-Determination Theory Based Exercise Intervention in a Group of Adult Exercisers; a Contextual Evaluation. University of Jyväskylä. Department of Sport Sciences, Master’s thesis in Sport and Exercise Psychology, 71 pages. According to the Self-determination theory, when the social context is autonomy supportive, people are motivated to internalize the regulation of important activities, and whereas when the context is controlling, self-determined motivation is undermined. Exercise is one of those important activities which when internalized would result in persistent engagement leading people to positive psychological and physiological outcomes (improved health, affect, self esteem). Although much experimental work has been done in these field examining the exercise context at all angles, no study to date has implemented and intervention based on tenets of the self-determination theory and reported its dynamic processes qualitatively. With the use of in-depth open interviews, ethnographic participant observation and supplemental questionnaires, this study aimed to investigate and evaluate the contextual environment in which the dynamic process of internalization occurs in a summer fitness program. 29 participants signed up to partake in this program. Using case studies to construct motivational profiles of each participant, motivational orientations are the subject of exploration as are the processes in the program that work in their gradual development. The last aim of this study is to evaluate SDT's contention ( Deci & Ryan, 1985, Ryan & Deci, 2000) that autonomous regulations (identified and intrinsic) are transgressed into more positive motivational consequences in the exercise domain, in this case, participation in activity outside the program, intentions to continue and persistence in exercise related behaviour. Results describe the implementation of the program and the process involved in providing an autonomy supportive environment. This environment combined with the use of intrinsic goal framing revealed conditions supportive of the basic psychological needs which facilitated internalization and integration within participants. Specifically, feeling important to the exercise leader, and relating to the exercise group facilitated internalization of values and behaviours endorsed in the program. Feeling competent showed the greatest influence of fully internalizing the regulation of exercise behaviours valued in the program. Whereas autonomous support resulted in the internalization of nutritional behaviours. In terms of goal setting, encouragement and support to think about the value of the behaviour to oneself facilitated identifying with and integrating the behavior’s value and regulation as well as resulting in positive psychological outcomes related to well-being, effort, intentions and persistence. This study also adds to current literature by addressing the often continuous report (Edmunds et al, 2008) of introjected regulations among female exercisers despite high internalization.